Occlusal Analysis in Natural Dentition: Systematic Review - Velásquez, Byron; Rodríguez, María; Mosquera, Verónica; Álvarez, Eddy; Chauca, Luis; Mena, Alexandra (European Journal of Dentistry, 2022)
This study aimed to evaluate the effectiveness of conventional occlusal analysis in contrast with digital occlusal analysis in natural dentition. Occlusal analysis allows the identification of normal and abnormal occlusal contact points that alter the craniomandibular cervical system. We searched for articles with keywords [[dental occlusion]], [[natural dentition]], [[occlusal adjustment]], [[Immediate Complete Anterior Guidance Development]] [[mastication]], [[bite force]], [[premature contact]], [[occlusal balance]] [[articulating paper]]], [[spray]], [[Occlusal contacts]], and [[bite strength]]. They were considered observational , odds ratio and case control studies. We found 189 items. After evaluating the abstracts and full texts of the articles, 10 papers met the inclusion criteria. It was found that occlusal analysis allows the identification of the relationship between poor occlusion and the sensitivity of the teeth due to occlusal trauma, which is also related to temporomandibular joint pain in dynamic occlusion. The contacts of greater strength were observed in nonfunctional cusps, 48%, without ruling out the functional cusps, 24%. Despite being the universal method of occlusal control to date, the use of joint paper, remains subjective compared to the digital occlusal control device. Posture is considered directly related to occlusal trauma and temporomandibular disorders; without proper occlusal analysis, a clear diagnosis of the patient's joint condition cannot be obtained. Digital occlusal analysis is more objective than traditional occlusal analysis.
Keywords: dental occlusion; occlusal adjustment; temporomandibular joint; mastication; bite force